Local community participation manifests sustainable tourism in the Batur Geopark Tourism Area - I Gede Wiramatika; Dewa Ayu Suryawati (School of Tourism, Universitas Ciputra Surabaya, 2026)
Batur as one part of the Batur Global Geopark, the urgency of this research is that a sustainable tourism planning and development model is very necessary to maintain the sustainability of culture, community environment, economy and way of life. Good planning and development will produce a good strategy in developing existing tourism resources. This study aims to examine the participation of local communities in the management of Batur Village as a tourist destination in Kintamani, regarding local community participation in the development of the Batur Geopark tourist area, the obstacles faced by local communities in the development of the Batur Geopark tourist area, and the efforts made by the Government in developing the Batur Geopark tourist area. The method in this study uses a mixed method of qualitative and quantitative. In this study, data were collected through interviews, observations, literature studies, documentation studies. The method of determining informants used key informants whose data came from people who were considered to know the research object such as, tourism industry entrepreneurs, community leaders, and the community then the data was analyzed using mixed qualitative descriptive data analysis techniques. The presentation of data analysis in this study was carried out qualitatively through verbal delivery with descriptive interpretative techniques. The results of this study indicate that community participation is divided into three parts, namely in the planning, management and evaluation stages involving community representatives from 15 villages that are included in the core zone of the Batur Geopark Tourism Area, but the development of the Batur Geopark Tourism Area has not been developed well and in accordance with the objectives of the geopark itself, there are still several activities that are contrary to the concept of a geopark that preserves the earth which can be seen from the increasing development of tourism facilities, the occurrence of land conversion, and the continued mining of sand and stone from lava from the eruption of Mount Batur.